2015
DOI: 10.1016/j.ejvs.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Outcomes of Severe Renal Impairment Following Ruptured Abdominal Aortic Aneurysm Repair

Abstract: Severe AKI is common following successful repair of rAAA. In this large case series of high-risk patients, OSR was associated with significantly higher rates of severe AKI compared with EVAR, despite the increased dose of contrast involved in EVAR and the older age of these patients. In turn, severe AKI was associated with higher mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 26 publications
3
40
0
1
Order By: Relevance
“…It also looks at whether there are differences in morbidity rates for patients treated at the weekend or out of hours in more detail than existing work – an important consideration given the high rates of morbidity experienced by this patient population14 15. The mortality rate for patients with ruptured aneurysms in this data set was 37·1 per cent, which is in line with figures from the recent IMPROVE study10, an RCT comparing endovascular and open repair strategies for ruptured AAA, giving confidence that outcomes are in line with other published figures from a UK cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also looks at whether there are differences in morbidity rates for patients treated at the weekend or out of hours in more detail than existing work – an important consideration given the high rates of morbidity experienced by this patient population14 15. The mortality rate for patients with ruptured aneurysms in this data set was 37·1 per cent, which is in line with figures from the recent IMPROVE study10, an RCT comparing endovascular and open repair strategies for ruptured AAA, giving confidence that outcomes are in line with other published figures from a UK cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated acutely for AAA also experience significant morbidity, as highlighted by recent reports14 15 focusing on acute kidney injury after ruptured AAA repair. Assessments of differences in morbidity rates for patients treated at the weekend are notably absent from previous studies, perhaps because the large administrative databases used tend not to record these outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that there is a 22-fold increase in the odds of mortality when postoperative ARF develops (OR, 22.30; 95% CI, 11.93-41.69; P < .001), which confirms results from prior studies. 7,39 Furthermore, dialysis and the extended length of stay in the hospital due to postoperative ARF add to the financial burden of EVAR on the health care system because hemodialysis is fully covered by Medicare services.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,6 The risk is even higher (26%) in patients with ruptured AAA who survived the first 24 hours after EVAR. 7 Of note, the 5-year follow-up of the Dutch Randomized Endovascular Aneurysm Management (DREAM) trial estimated an average decline of estimated glomerular filtration rate (eGFR) of 0.9 (63.9) mL/min/1.73 m 2 per year after EVAR, and this decline was similar to what is observed after open repair. 8 …”
mentioning
confidence: 87%
“…AKI in the context of emergency ruptured AAA repair is well described and expected given the nature of the typical in extremis presentation (12). Again, open surgical repair, especially if suprarenal clamping is required intraoperatively, inevitably results in some renal ischemia (13).…”
mentioning
confidence: 99%